IMPLIKASI PERUBAHAN KURIKULUM PENDIDIKAN PADA SISTEM PENDIDIKAN TARUNA TERHADAP PENCAPAIAN KUALITAS TARUNA GUNA MENDUKUNG KETAHANAN SATUAN (Studi Di Akademi Militer, Magelang, Jawa Tengah) - Rita Kuntarti (Jurnal Ketahanan Nasional, 2014)
Curriculum model was highly affected the Military Academy education’s output competence and quality. The curriculum design had significant effect on unit resilience on the Military academy internal level. The curriculum modification was highly needed although procedural provisions had to be attended. The purpose of this research was to discover the implication of education curriculum modification of cadets’ education system on cadets’ quality achievement to supported the unit resilience. The curriculum needed to be re-evaluated due to the material, activities and the implication which was conducted with interview technique and observation. The collected data was analyzed and presented in a paper. Military material should be more focused on education special character with defense contextual character, the cadets’ intense activities has to be re-evaluated. Therefore each unit needed to awared and committed on the perception of the limited psychic and physic of the cadets.Keywords: Curriculum, Quality, Unit Resilience